Respiratory Protective Equipment (RPE) Standard – Disposable Filtering Half Mask on N95, FFP2 and KN95 - Osman, Baderin; Leman, Abdul Mutalib Bin; Rahman, K.A; Mat Hasan, Nik Normunira; Seong, Ng Goot; Muzarpar, M.Syafiq; Mohamad, Salwa; Mohamad, Halah (Journal of Advanced Industrial Technology and Application, 2022)
Workplace and work activities issued many harmful substances that contaminating the air. Therefore, the employer needs to select a standard disposable filtering half mask for the workers in order to prevent them from harmful substance. This study presents current literature search of RPE standard in certain countries such as United States (US), United Kingdom (UK) and China. The selection of the standard disposable filtering half masks has to guide by Assigned Protection Factor (APF) according to working condition activity. The APF includes the suitability factor such as effectiveness towards particle and gas/vapour, continuous wear time and APF types (4, 10, 20, 40, 200, and 2000).